2019
DOI: 10.1007/s13238-019-0617-0
|View full text |Cite
|
Sign up to set email alerts
|

Basic and translational aging research in China: present and future

Abstract: The percentage of elderly people in the world is increasing at an unprecedented pace; so it is in China, which has the world's largest population and a high ratio of the seniors (aged 60 and above) to working-age adults. The growing elderly population is presenting a major social challenge. Accordingly, it is not only imperative as a national strategic demand but also promises great scientific values to understand the biological process of aging, explore the mystery of healthy aging, delay the aging process, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 87 publications
(102 reference statements)
0
26
0
Order By: Relevance
“…It is delightful to witness the progress of basic and translational ageing research in China, as supported by increases in the number of grants and funding opportunities, as well as by rising numbers of high profile publications and discoveries ( He et al, 2019c ). Joint efforts from the government and stakeholders of each and every sector should be encouraged to nurture an elderly-friendly society, of most import are reforming the Social Support System to support China’s ageing society, and the introduction of health service/investment interventions aimed at reducing inequalities in health among older people in China.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It is delightful to witness the progress of basic and translational ageing research in China, as supported by increases in the number of grants and funding opportunities, as well as by rising numbers of high profile publications and discoveries ( He et al, 2019c ). Joint efforts from the government and stakeholders of each and every sector should be encouraged to nurture an elderly-friendly society, of most import are reforming the Social Support System to support China’s ageing society, and the introduction of health service/investment interventions aimed at reducing inequalities in health among older people in China.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…5 The 2013 “China Aging Development Report” noted that the severity of the aging problem in China was unprecedented. 6 Population aging is an important concern because age is a major risk factor for many debilitating and life-threatening conditions, including cancer, cardiovascular disease, and neurodegeneration. 7 Dementia is a symptom of various neurodegenerative diseases associated with aging.…”
Section: Introductionmentioning
confidence: 99%
“…20 According to a national survey conducted by the National Bureau of Statistics, as at the end of 2018, the number of older adults aged at least 60 years in China had reached 249 million, accounting for approximately 17.9% of the total population. 21 This study found that the incidence of UTI was higher in females than in males. America found the same situation that the lifetime risk of UTI for females is about 50% and about 20% for males.…”
mentioning
confidence: 75%